Analisis Pengelolaan Arsip Kepesertaan Inaktif pada BPJS Ketenagakerjaan - Deverin Dwi Purwanti (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to determine how inactive membership archives are managed at the BPJS Ketenagakerjaan Jakarta Rawamangun Branch. The background of this study is based on the importance of good management of inactive membership archives to support smooth administrative services, considering that inactive membership archives still have utility value, especially as evidence of claims and membership audits. The research method used is a descriptive method with a qualitative approach, through observation techniques, interviews, and documentation studies. The results of the study indicate that the management of inactive membership archives includes the stages of creation, use, maintenance, and reduction of archives which are carried out according to procedures from the head office. Archives are arranged based on the Company Registration Number (CRN) so that it is easy to find archives when needed. However, archive management is still faced with several obstacles, such as limited storage space, the process is still carried out manually, and the lack of workers with special competencies in the fields of archiving BPJS Ketenagakerjaan Jakarta Rawamangun Branch has also attempted to overcome these obstacles by digitizing membership archives, although its implementation has not been fully integrated into an adequate electronic archive management system. The conclusion of this study is that the management of inactive membership archives at BPJS Ketenagakerjaan Jakarta Rawamangun Branch has been running quite well, but still needs to be improved, especially in strengthening technology, adding competent workers, and improving supporting facilities and infrastructure. This is important so that the archive management process can run more effectively and efficiently, and support the achievement of excellent service to participants.